Simulação pelo modelo hydrus 2d da dinâmica de água e transporte de potássio em um cambissolo do semiárido potiguar - Arruda, Luiz Eduardo Vieira de (Universidade Federal Rural do Semi-Árido, 2018)
In arid and semiarid regions of the Brazilian Northeast the water is a scarce resource and its excessive removal in recent decades, is resulting increased of concentration of salts and, consequently, reducing their quality. It is necessary to know the water dynamics and the solutes transport in the soil, when they are applied on the soil surface, in order to predict their spatial distribution, which is fundamental to establish the best way to monitor moisture, salinity and nutrients in the root system zone of crops. For this, it is necessary that the irrigator use tools that assist him in the management of the agricultural production. The objective of this work was to evaluate the use of HYDRUS 2D software in the simulation of water dynamics and the transport of potassium in the soil inside the wetted bulb under surface drip irrigation. For this, an experiment was carried out in a controlled environment in pots of approximately 60 L filled with soil (Inceptisol), where were applied three different flow rates (0.72, 1.52 and 2.50 L h-1), and three concentrations of potassium (0.165, 0.450 and 0.750 mg cm-3) via surface drip irrigation. To do so, the experiment was conducted with the purpose of obtaining input data for the simulation with the HYDRUS 2D software and data for validation and comparison with the data obtained in the software simulation. The same consisted of initial characterization of the soil and the development of the digital tensiometers and electrical conductivity sensors of the soil with their respective calibrations; filling the pots; conduction and monitoring of the experiment during the application of 5.0 L of solution (irrigation) and subsequent redistribution up to 72 h; at the end, determination of the soil physical attributes. Breakthrough Curves (BTC) were also elaborated to determine the potassium transport parameters in the soil; simulations were performed using the HYDRUS 2D model; and later, the performance statistical analysis of the HYDRUS 2D model using the Root Mean Square Error (RMSE) and the Mean Absolute Error (MAE); and, finally, the sensitivity analysis of the model. A good fit was observed between the observed and simulated data with the model, for the distribution and redistribution of water and the transport of potassium in the soil, with low values obtained from RMSE and MAE. It can be concluded that the model provided robust results for the distribution and redistribution of water in the soil, in protected environment, under surface drip irrigation, in relation to the data observed experimentally; as well as for simulations of transport and redistribution of potassium in the soil under different concentrations of the solution applied
Keywords: Manejo da irrigação; Irrigação por gotejamento superficial; Fluxo de água no solo; Transporte de soluto no solo; Modelagem matemática; Irrigation management; Surface drip irrigation; Water flow in the soil; Solute transport in the soil; Mathematical modeling; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO